2011
DOI: 10.1089/scd.2010.0281
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine and Epigenetic Control of Trophectoderm Differentiation from Human Embryonic Stem Cells: The Role of Bone Morphogenic Protein 4 and Histone Deacetylases

Abstract: Our understanding of paracrine and epigenetic control of trophectoderm (TE) differentiation is limited by available models of preimplantation human development. Simple, defined media for selective TE differentiation of human embryonic stem cells (hESCs) were developed, enabling mechanistic studies of early placental development. Paracrine requirements of preimplantation human development were evaluated with hESCs by measuring lineage-specific transcription factor expression levels in single cells and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 90 publications
(134 reference statements)
3
42
0
Order By: Relevance
“…1B). This phenomenon has been described earlier (1,(9)(10)(11). However, when inhibitors [A83-01 (A) and PD173074 (P)] that block the SMAD2/3 and MEK1/2 signaling pathways, respectively, were added simultaneously with BMP4 (BMP4/A/P), the ESC phenotype of the colonies was lost within 48 h. The transition to a flattened epithelium had progressed completely and quite uniformly throughout all colonies by this time point.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…1B). This phenomenon has been described earlier (1,(9)(10)(11). However, when inhibitors [A83-01 (A) and PD173074 (P)] that block the SMAD2/3 and MEK1/2 signaling pathways, respectively, were added simultaneously with BMP4 (BMP4/A/P), the ESC phenotype of the colonies was lost within 48 h. The transition to a flattened epithelium had progressed completely and quite uniformly throughout all colonies by this time point.…”
Section: Resultssupporting
confidence: 71%
“…This differentiation occurred without extensive generation of mesoderm, endoderm, and ectoderm derivatives, as judged by microarray analysis of transcribed genes, although a low level of expression of genes characteristic of mesoderm and endoderm did occur. This model has become widely used (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) to study an aspect of early human development that is not easily addressed otherwise because of lack of access to human embryos. Over the course of these studies it was demonstrated that the key to obtaining differentiation primarily to TR rather than to other lineages when using BMP4 as the triggering agent was to exclude FGF2, a factor required for maintenance of hESC (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…One previous study developed a minimal medium for trophoblast induction but also used high BMP4 concentrations and focused on the evaluation of CDX2 as the primary TE marker (17). Because high-dose BMP4 also can induce mesoderm (23), we asked whether, in that minimal medium (17), low-dose BMP4 (10 ng/mL) by itself is able to initiate trophoblast differentiation of hPSCs into CTBs, as evaluated by a comprehensive panel of markers, including p63 and CDX2. We initially used WA09/H9 ES cells (ESCs) but also tested this protocol on WA01/H1 and SIVF21 ESCs as well as on induced pluripotent stem cells (iPSCs) derived in the L.C.L.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2002, when Xu et al (15) first published the finding that bone morphogenetic protein 4 (BMP4) induces the expression of trophoblast-related genes in hPSCs, multiple groups have used these cells as a model for studying trophoblast lineage specification (16)(17)(18)(19)(20)(21)(22). The majority of these studies, including our own (21), have used BMP4…”
mentioning
confidence: 99%
“…For trophectoderm differentiation, hPSCs were first treated with a StemPro-based basal medium (Erb et al, 2011) for 2 days, then cultured in feeder-conditioned medium supplemented with 10 ng/ml human BMP4 (StemRD) for the indicated number of days.…”
Section: Human Pluripotent Stem Cell Culture and Differentiationmentioning
confidence: 99%